Análisis de la productividad y rendimiento de la mano de obra para algunas actividades constructivas del sistema electromecánico en Torres de Parqueo UCR - Rojas-Zúñiga, Beatriz (Instituto Tecnológico de Costa Rica, 2017)
The objective in the development of this graduation project is to establish the performance and productivities of the labor in constructive activities of the electromechanical part in charge of the company CMC contratista electromecánica, in the Torres de Parqueo project, located at the headquarters Of the University of Costa Rica. In order to determine the productivity and performance, data collection instruments were designed and measurements were taken by means of the implementation of engineering and probabilistic methods such as labor sampling and equipment balance, which allowed to obtain the percentages of productive work, contributory and unproductive of the workers as well as the time allocated to each activity. The work force performance were analyzed for the canalization and wiring of the receptacle systems and the lighting, and for the placement of the fire suppression system. A database has been developed for the company to store and update the performance of the workforce in future projects. A brief survey was applied that, together with the daily observation of the processes, the results that the samples offered allowed to identify the main factors that negatively intervene in the development and the performance of the workers in the different activities.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2017.
Keywords: Productividad; Rendimiento; Mano de obra; Construcción; Desempeño; Trabajadores; Eficiencia